Effect of vitamin D supplementation on inflammation: protocol for a systematic review. Issue 4 (5th April 2016) - Mousa, Aya; Misso, Marie; Teede, Helena; Scragg, Robert; de Courten, Barbora
Abstract : Introduction: The extraskeletal role of vitamin D is being increasingly recognised. This has important clinical implications, as vitamin D deficiency has reached epidemic proportions worldwide. Vitamin D has proposed anti-inflammatory properties, yet the role of vitamin D supplementation in reducing inflammation remains largely unknown. The purpose of this review is to investigate the impact of vitamin D supplementation on inflammation, and to identify relevant knowledge gaps in the field. Methods and analysis: Medline, CINAHL, EMBASE and All EBM will be systematically searched for randomised controlled trials (RCTs) and systematic reviews of RCTs, comparing vitamin D supplementation with placebo, usual care or other pharmacological or non-pharmacological interventions. One reviewer will assess articles for eligibility according to prespecified selection criteria, after which 2 independent reviewers will perform data extraction and quality appraisal. Meta-analyses will be conducted where appropriate. Ethics and dissemination: Formal ethical approval is not required as no primary data is collected. This systematic review will identify potential clinical implications of vitamin D deficiency and supplementation, and will be disseminated through a peer-reviewed publication and at conference meetings, to inform future research on the efficacy of vitamin D supplementation for inflammation and inflammatory diseases. PROSPERO registration number: CRD42016037104.